1995
DOI: 10.1136/ip.1.4.223
|View full text |Cite
|
Sign up to set email alerts
|

'What I said' versus 'what you heard': a comparison of physicians' and parents' reporting of anticipatory guidance on child safety issues.

Abstract: Objective Unintentional injuries are the number one cause of death for infants. Many of these injuries could be prevented if parents took additional safety precautions. In this study physicians' and parents' perspectives regarding the part that physicians play in educating first time parents about child safety issues were compared. Methods-All pediatricians and family physicians in London, Ontario were surveyed by mail (68% return rate) regarding their practices, attitudes, and beliefs related to parent educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…In spite of these recommendations, several studies have indicated that injury prevention is either not discussed at all or covered only briefly during the course of routine visits [32,33]. This is not an uncommon finding for preventive service delivery in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these recommendations, several studies have indicated that injury prevention is either not discussed at all or covered only briefly during the course of routine visits [32,33]. This is not an uncommon finding for preventive service delivery in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…[4;7-11] Furthermore, there is some evidence that providers avoid or discourage parental disclosure of psychosocial concerns, [12] which may affect parents' willingness to discuss such concerns in future visits. [13] In fact, parents are often hesitant to discuss psychosocial concerns with their child's pediatrician. [5,9,14] Only half of parents who either have psychosocial concerns or a child with a psychiatric diagnosis disclose these concerns to their child's pediatrician.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with children suggests that a patient-centered approach [25], and more specifically, use of interpersonal communication skills such as empathy, praise and collaboration [26][27][28] are associated with positive outcomes as well. It may be particularly important to assess this communication style with families with psychosocial concerns given that these families represent a growing segment of the patients seen by pediatricians [1], these encounters may be at increased risk for ineffective parent-provider communication [5,9,[12][13][14], and there are new recommendations that pediatricians employ collaboration, empathy, and praise with families when addressing psychosocial concerns. [15] The present investigation asked: How do parents of children with psychosocial problems perceive their child's provider's interpersonal communication skills?…”
Section: Introductionmentioning
confidence: 99%
“…Los pediatras están en una posición privilegiada para abordar estos temas, generar conciencia y buscar estrategias de prevención junto con la familia y la comunidad. [6][7][8][9][10][11][12][13][14] En nuestro trabajo, se observó que, a diferencia de la anterior encuesta, 5 los pediatras de menor antigüedad adquirían más conocimientos sobre prevención de lesiones durante el pregrado y durante la residencia, lo que revelaría una mayor preocupación de las instituciones formadoras acerca de este tema. Siguiendo con esta tendencia, los profesionales que habían terminado más recientemente su entrenamiento pediátrico abordaban más tópicos de supervisión/guías anticipatorias en las consultas de niño sano.…”
Section: Discussionunclassified
“…[7][8][9][12][13][14][15] El modo de llevarla a cabo se basaba, principalmente, en la transmisión verbal, que era poco efectiva. 5,[10][11][12] Este trabajo tiene fortalezas y debilidades.…”
Section: Discussionunclassified